Learning from Each Other: A History of Russian-native Contacts in Late Eighteenth-Early Nineteenth Century Exploration and Mapping of Alaska and the Aleutian Islands - Postnikov, Alexey V. (The International Hydrographic Review, 2005)
The paper discusses contacts between educated European hydrographers and the native population of Alaska and the Aleutian Islands during their exploration and occupation by the Russians (late XVIII c. - 1867). The author, on the basis of his studies in Russia, the USA and the United Kingdom has found that the contacts were very active and helpful for the hydrographic surveys and the compilation of charts for the waters and coast of Russian America. The paper shows that the native tribes of these lands (Aleuts, Eskimos and others) had created their own original very skilled methods of navigation.